Performance of reinforced concrete wall foundation connection under lateral static load / Aida Kartini Saidin - Saidin, Aida Kartini (Faculty of Civil Engineering, 2012)
Steel fabric reinforced concrete wall foundation is considered as an innovative construction method in Malaysia to reduce weight on foundation. This type of wall foundation may require sequ encial analysis in making an effective product that gives advantanges in all aspects and gives better performance.This research involved laboratory experimental work on three reinforced concrete wall foundation samples.The wall is reinforced with steel fabric of size B7 and concrete Grade 30 mix with steel fabric. The wall foundation samples were tested under lateral static load with the load applied upper of the wall he ight wall. The support condition was considered as fixed at the lower end foundation. The ultimate load sustained by the samples is 30kN with maximum displacement of 35mm before failure. From the observation, there are failure cracks along the connection and at the side of the connection that influence the strength of the connection itself. Wall foundation 1 started to crack when load reach the value of 5kN with maximum deflection of 15.44mm while for sample 2, wall foundation started to crack when applied load reach the value of 5.97kN with maximum deflection of 10.37mm. Lastly, for sample 3, wall foundation started to crack when applied load reach the value of 8.58kN with maximum deflection of 20.13mm. From research the maximum bending stress for sample 1, 2 and 3 is 3.75 kN/mm2, 7.36 kN/mm2 and 9.72 kN/mm2 respectively. Modulus of elasticity for sample 1, 2 and 3 are 8.78862 xlO-3 N/mm2, 9.9571 xlO-3 N/mm2 and 0.1180 xlO-3 N/mm2 respectively. Therefore, maximum modulus of elasticity usually occurs at connection of wall foundation. Besides that, lateral static load has affect on the compressive strength, fracture energy and ductility thus inhabit the crack propagation of the reinforced concrete wall foundation.